1994
DOI: 10.3758/bf03206946
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity and pop-out in visual search

Abstract: In this paper, we report that when the low-level features of targets and distractors are held constant, visual search performance can be strongly influenced by familiarity. In the first condition, a ILl was the target amid ins as distractors, and vice versa. The response time increased steeply as a function of number of distractors (82 msec/item). When the same stimuli were rotated by 90°(the second condition), however, they became familiar pattems-2 and S-and gave rise to much shallower search functions (31 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
275
4
10

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(321 citation statements)
references
References 26 publications
32
275
4
10
Order By: Relevance
“…Research has consistently shown that icon familiarity determines the speed and accuracy with which icons and objects can be identified (Ben-Bassat & Shinar, 2006;Chan & Ng, 2010;Lesch et al, 2011;Lui, 2005;Shinar et al, 2003;Wang, Cavanagh & Green, 1994;Wolfe & Alvarez, 2011). When compared to other icon characteristics, it appears to be the most important determinant of ease of identification (Isherwood & McDougall, 2007;McDougall & Isherwood, 2009).…”
Section: Familiaritymentioning
confidence: 99%
“…Research has consistently shown that icon familiarity determines the speed and accuracy with which icons and objects can be identified (Ben-Bassat & Shinar, 2006;Chan & Ng, 2010;Lesch et al, 2011;Lui, 2005;Shinar et al, 2003;Wang, Cavanagh & Green, 1994;Wolfe & Alvarez, 2011). When compared to other icon characteristics, it appears to be the most important determinant of ease of identification (Isherwood & McDougall, 2007;McDougall & Isherwood, 2009).…”
Section: Familiaritymentioning
confidence: 99%
“…Chun and Jiang (1998) discuss a number of factors that influence visual deployment (see also Kellman, 2002;Wolfe, 1994;Yantis, 1996). These include bottom-up, image-driven factors such as salience (Bravo & Nakayama, 1992;Egeth, Jonides, & Wall, 1972;Theeuwes, 1992;Treisman & Gelade, 1980) and top-down factors such as familiarity (Wang, Cavanagh, & Green, 1994) and expectancy (Loftus & Mackworth, 1978;Miller, 1988;Shaw, 1978;Shaw & Shaw, 1977). Such factors are clearly important in detecting anomalies, but they cannot be the whole story.…”
Section: Detecting Anomalous Features and Alignable Differencesmentioning
confidence: 99%
“…Visual attention has been shown to be driven by both the salience of the stimuli (bottom-up) and looking for a specific predefined feature (guided or top-down search) (Yantis and Jonides 1984). studies have shown that some features "pop-out" requiring similar search times for displays with few as well as many distractors (Wang et al 1994;treisman and Gelade 1980), while other targets result in "inefficient" search with longer search times for displays with more distractors. the large majority of visual search studies have focused on features defined by specific visual information (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…the large majority of visual search studies have focused on features defined by specific visual information (e.g. color, shape, or location) all of which are coded within the visual system (Duncan and humphreys 1989;Wang et al 1994). It has been suggested that guided search involves an attentional modulation of the specific feature of the search set and has been shown to enhance cortical activity in regions selective to that feature (corbetta et al 1990).…”
Section: Introductionmentioning
confidence: 99%